Comparison of Properties of the Persian Version of the Sensory Profile 2 in Children with Autism Spectrum Disorder and typical Individuals - Mirzakhany, Navid; Mahmoudi, Ebrahim; Ghanouni, Parisa; Shahbazi, Marjan (Journal of Clinical Physiotherapy Research, 2020)
Introduction: Autism spectrum disorder (ASD) is a childhood developmental condition that affects social-emotional skills and communication. Sensory processing represents a significant factor in influencing the behavioral responses. However, it has been shown that children with ASD usually experience some sensory difficulties. The purpose of this study was to evaluate the sensory processing in children with ASD to identify which domains are mainly affected. Methods: The population of this study included 30 children with ASD aged between 1 to 5 years and 30 age- and gender-matched typically developing individuals. Sensory processing was assessed through a parent-reported questionnaire of the child sensory profile 2. Multivariate Analysis of Variance (MANOVA) was used to analyze the data. Results: The findings of this study showed that individuals with ASD had a significant difference in all sensory processing components of the sensory profile 2 compared with the age-matched peers (P<0.05), except for the two components named touch processing and body position (P˃0.05). Conclusion: Since the present study shows that there is a difference between a number of sensory processing components in children with ASD and typically developing peers, it is suggested that therapists should perform this test in other groups of vulnerable populations such as developmental delay, attention deficit hyperactivity disorder, learning disorder, infertility, and Down syndrome. Keywords: Autism Spectrum Disorder, Sensory Processing, Sensory Profile 2